+0  
 
0
41
1
avatar

I'm just a little confused on how they factored the numerator in this step:

 

Where did the 1 come from?

 

Thank you :)

 Feb 22, 2019
 #1
avatar+99309 
0

I am not sure which 1 you are referring to, but....

 

\(\frac{sinxcosx-sinx}{cos^2x-1}\\~\\ \qquad \text{Factorise the top}\\~\\= \frac{-sinx(-cosx+1)}{cos^2x-1}\\~\\ \qquad Sin^2x+cos^2x=1 \qquad so\\~\\ =\frac{-sinx(1-cosx)}{-sin^2x}\\~\\ \qquad \text{cancel}\\~\\ =\frac{1-cosx}{sinx}\\~\\\)

.
 Feb 22, 2019

10 Online Users

avatar
avatar